An examination of a few antecedents of green creativity using structural equation modeling - Sulphey, Manakkattil Mohammed Ismail; Al-Kahtani, Nasser Saad; Senan, Nabil Ahmed Mareai; Adow, Anass Hamad Elneel (Creativity Studies, 2023)
Green creativity is developing original and practical ideas that could result in green products and services. Moreover, as stakeholders favour environmentally responsible policies and practices, organizations are shifting towards green business models and initiatives. Though there is extensive literature on various green behaviours, there is a lack of a clear understanding of what motivates green creativity. The present study bridges this research gap by identifying employee green behaviour, green shared vision, and green value as antecedents of green creativity. The study used structural equation modeling, based on data from 384 respondents, to analyze the relationship between the variables. The findings revealed significant positive relationships between the variables, supporting the model developed for the study. The study’s findings can help organizational leaders to enhance green creativity and consequent innovations by encouraging and facilitating employee green behaviour, green shared vision, and green value.